Developmental Concepts: Qualitative Overview of Nigeria's Experience: Konsep Pembangunan: Tinjauan Kualitatif Pengalaman Nigeria - Majekodunmi, Samuel Ayodele; Olajide-Arise, Temi Omovigho (LPPM Universitas Pelita Bangsa, 2025)
The incidence of best brains and hands migrating from Nigeria to settle for a new life in the developed world has persistently increased. Similarly, organizations are relocating from Nigeria due to the rising cost of operations. Practically, all sectors in the Nigerian economy have continued to face shortages of skilful personnel. However, the health sector seemed to be the most affected. The concern about the current situation of low economic development leading to an exodus of energetic Nigerians seeking greener pastures elsewhere necessitates this study titled